CONVECTOR WATER EXCHANGE ANALYSIS IN FEROZA SERVICE CARS WITH DIFFERENT RUNNING VARIATIONS - Celcio Novian Primananda; Fransiskus A. Widiharsa; Agus Mulyono (TRANSMISI, 2019)
The cooling system at work of a gasoline engine functions as a protective engine by absorbing heat. Engine heat is produced from combustion of fuel in the cylinder. The heat is something that is deliberately created to produce energy, but if left unchecked will cause excessive heat (over heating effect). Excessive heat is the cause of changing mechanical properties as well as the shape of the engine components. The purpose of the study was to determine the temperature of the cooling water on the convector / radiator on the convector / radiator on the ferroza official car that has been modified using a multi point injection system. This cooling system does work simultaneously with the combustion system, so as to produce engine work which is the output of the engine. The cooling system is a support system of engine work. The system is not the main system that is the basis of the engine  to do work and effort, but both systems have a very vital function.